2012
DOI: 10.1097/brs.0b013e31823765af
|View full text |Cite
|
Sign up to set email alerts
|

Total Motion Generated in the Unstable Cervical Spine During Management of the Typical Trauma Patient

Abstract: We have demonstrated the total angular motion incurred to the unstable cervical spine as experienced by the typical trauma patient from the field to stabilization in the operating room using the best compared with the most commonly used techniques. As previously reported, using log-roll techniques consistently results in unwanted motion at the injured spinal segment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
(3 reference statements)
1
4
0
Order By: Relevance
“…Our group has previously evaluated various spine-boarding transfer techniques. 6 9 , 14 , 23 , 24 Results of these studies support our current findings and suggest that the lifting techniques may be a better alternative to the LR. Del Rossi et al 7 specifically looked at these 3 methods of spine boarding and found less motion with the use of lifting techniques as compared with the LR.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our group has previously evaluated various spine-boarding transfer techniques. 6 9 , 14 , 23 , 24 Results of these studies support our current findings and suggest that the lifting techniques may be a better alternative to the LR. Del Rossi et al 7 specifically looked at these 3 methods of spine boarding and found less motion with the use of lifting techniques as compared with the LR.…”
Section: Discussionsupporting
confidence: 88%
“…In a later study examining typical movements and transfers of a trauma patient, in addition to spine boarding, it was again shown that the LR results in additional motion at an unstable cervical spine injury. 23 These studies did not evaluate the maneuvers with protective football equipment in place. Dealing with such a situation requires proper training and possibly alternative techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In two recent studies, for both a cervical[19] and thoracolumbar injury,[20] we evaluated the cumulative effects of repeated log roll maneuvers during sequential stages of trauma management. Each of these studies tested the motion that occurred during spine board placement, spine board removal, bed transfers, lateral therapy, and prone positioning in the operating room.…”
Section: Resultsmentioning
confidence: 99%
“…to different diagnostic locations and imaging facilities), making this an important phase of care to be evaluated. The studies by Prasarn and colleagues[1920] analyzed the motion that occurs when a patient is transferred between hospital beds. One common practice for performing bed transfers is to log roll the patient onto a transfer board (sliding board or roller board) and then shift the patient from one bed to the adjacent bed.…”
Section: Resultsmentioning
confidence: 99%
“…This can be done for example by placing the mattress on a scoop stretcher. Because the mattress can be folded around the body, immobilisation is superior to that achieved using a spineboard, both objectively [62,[65][66][67][68] and subjectively [66,68].…”
Section: Advantages and Disadvantages Of Using A Spineboard Or Vacuum Mattressmentioning
confidence: 99%